The Significance and Utilisation of Biomimetic and Bioinspired Strategies in the Field of Biomedical Material Engineering: The Case of Calcium Phosphat-Protein Template Constructs - Šupová, Monika (Materials (Basel, Switzerland), 2020)
This review provides a summary of recent research on biomimetic and bioinspired strategies applied in the field of biomedical material engineering and focusing particularly on calcium phosphate-protein template constructs inspired by biomineralisation. A description of and discussion on the biomineralisation process is followed by a general summary of the application of the biomimetic and bioinspired strategies in the fields of biomedical material engineering and regenerative medicine. Particular attention is devoted to the description of individual peptides and proteins that serve as templates for the biomimetic mineralisation of calcium phosphate. Moreover, the review also presents a description of smart devices including delivery systems and constructs with specific functions. The paper concludes with a summary of and discussion on potential future developments in this field.
Keywords: calcium phosphate; protein template; biomimetic